Data collected to measure the impact of problem-based learning and document physics classroom practices among Ugandan secondary schools - Kanyesigye, Stella Teddy; Uwamahoro, Jean; Kemeza, Imelda (Data in Brief, 2022)
This dataset comprises data collected from three measures; (a) 419 students who completed the mechanical waves conceptual survey (MWCS), (b) the same students (419 students) who completed the views about sciences survey (VASS), and (c) 152 physics lessons that were observed from 22 teachers using reformed teaching observation protocol (RTOP). The data were collected from 19 schools in Mitoma district, Southern western Uganda, for the first author’s doctoral re- search project in physics education pursued at the University of Rwanda College of Education (URCE). The data were collected from February to April 2021, while the training for the problem-based learning (PBL) approach was delivered to teachers from 10 to 11 February 2021. The students were split into four groups (with a Solomon four-square de- sign), and data includes pre-and post-test measures from be- fore and after teacher instruction on problem-based learning. On the side of teachers, 72 classrooms were observed in classrooms taught by teachers who were trained in PBL, while 80 were observed in the classroom taught by teachers who were not trained in PBL. This dataset is in the form of raw data, and it can be analyzed in various forms, such as students’ performance and conceptual understanding of mechanical waves, their attitudes toward science, and teacher and students’ classroom practices. It provides room for re- searchers to explore, dig deep into, and reuse it for various purposes such as experimental versus control trials, students’ gender, school characteristics, etc. Policymakers and educationists would also explore and get insights into Ugandan classrooms’ teaching and learning practices.
Keywords: Data; Classroom observation; Mechanical waves; Problem-based learning; Views about science; Uganda